Designing a Hypothetical Learning Trajectory using the Local Wisdom of South Sumatera as a Context through Hybrid Learning - Utari, Rahma Siska; Putri, Ratu Ilma Indra; Zulkardi (Mathematics Education Journal, 2024)
Data visualization and interpretation are important statistical literacy skills for prospective mathematics teachers. Intervention in the learning process can be done by designing Hypothetical Learning Trajectory (HLT) and integrating local wisdom which can develop students' statistical literacy skills. This research aimed to describe the HLT design with the topic of data visualization using the local wisdom of South Sumatra through hybrid learning. The method used was design research, with three stages, namely: preparation for the experiment, the design experiment, and the retrospective analysis. In this study, the design experiment was carried out at the pilot experiment stage. A total of 10 students from the mathematics education study program participated in this research. Data was collected through observation, interviews, and documentation. The HLT was compared with the Actual Learning Trajectory (ALT) that occurred in the class. The results of the research show that students can be given contextual problems using the local wisdom context of South Sumatra, explore data visualization in various forms of data presentation, and interpret data from the visualization that have been created. Data visualization can help students understand and interpret data better.